The Effect of DLPFC Stimulation Compared to Mindfulness Exercises on Cognitive Performance in Children with Attention Deficit Hyperactivity Disorder - Amini , Ashraf; Eslamizad , Amineh; Hosseini , Mehdi; Moradizade , Namaan (International Journal of Sport Studies for Health, 2024)
Objective: Mindfulness programs and transcranial direct current stimulation (tDCS), particularly of the dorsolateral prefrontal cortex (DLPFC), are increasingly used for therapeutic purposes in Attention Deficit Hyperactivity Disorder (ADHD). The aim of the present study was to investigate the effect of DLPFC stimulation compared to mindfulness exercises on cognitive performance in children with ADHD.Materials and Methods: In this quasi-experimental study, 45 children with ADHD participated in a between-group design (mindfulness program, DLPFC stimulation, and sham stimulation) with two measurement phases (pre-test and post-test). All subjects underwent 15 intervention sessions according to their respective group. At various stages, participants were tested on cognitive flexibility (Wisconsin Card Sorting Test) and working memory (Wechsler Intelligence Scale).Findings: The results of the composite analysis of variance showed significant main effects of time, group, and the time-group interaction for the research variables, including cognitive flexibility (perseverative error and total error) and working memory. Post hoc test results indicated that the DLPFC stimulation group had significantly better scores in cognitive flexibility (perseverative error and total error) and working memory compared to the mindfulness group.Conclusion: Hypoactivity of the dorsolateral prefrontal cortex underlies executive function deficits in individuals with ADHD, and transcranial direct current stimulation increases activation of the dorsolateral prefrontal cortex through anodal stimulation.